How Wetting Properties Influence the Wear of Radial Lip Sealing Systems. Issue 1 (19th October 2022) - Fricker, Philipp; Baumann, Matthias; Bauer, Frank
Abstract: Increased wear on radial lip seal systems is observed when sealing modern lubricants, such as polyglycols and esters. This can impair the function of the sealing system and ultimately lead to leakage. This work, carried out within the AiF research project "Welleneinlauf" (wear of counter faces) [1], shows methods to identify and predict excessive wear of radial lip sealing systems based on their wetting properties and pumping rate. The knowledge gained will support users by providing faster and more cost‐effective testing methods early in the design process, thus enables a significant increase in the service life of radial lip sealing systems. Abstract : Increased wear on radial lip seal systems is observed when sealing modern lubricants. This can impair the function of the sealing system and ultimately lead to leakage. This work shows methods to identify and predict excessive wear of radial lip sealing systems. This supports users by providing faster and more cost‐effective testing methods, thus enabling an increase in the service.